Geminal Difunctionalization of Vinylarenes: Concise Synthesis of 1,3-Dioxolan-4-ones - Balaji, Pandur Venkatesan; Chandrasekaran, Srinivasan (Synlett, 2019)
We report a straightforward method for the synthesis of five-membered 1,3-dioxolan-4-ones by an unprecedented oxidative alkene geminal difunctionalization strategy using α-hydroxy carboxylic acids. Under the geminal oxidative addition conditions, various substituted α-hydroxy carboxylic acids and styrenes containing a variety of substituents, including β-substituted styrenes, were effectively coupled regioselectively (anti-Markovnikov) with an isobutyl-substituted chiral α-hydroxy carboxylic acid, providing an annulation with excellent diastereoselectivity. An aryl migration in the semipinacol rearrangement leading to geminal oxidative addition of the α-hydroxy carboxylic acids was confirmed by deuterium-labelling and control studies.
Keywords: dioxolanones; geminal difunctionalization; regioselectivity; rearrangement; aryl migration